2020
DOI: 10.2337/dc19-2391
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization for Lactic Acidosis Among Patients With Reduced Kidney Function Treated With Metformin or Sulfonylureas

Abstract: To compare the risk of lactic acidosis hospitalization between patients treated with metformin versus sulfonylureas following development of reduced kidney function. RESEARCH DESIGN AND METHODS This retrospective cohort combined data from the National Veterans Health Administration, Medicare, Medicaid, and the National Death Index. New users of metformin or sulfonylureas were followed from development of reduced kidney function (estimated glomerular filtration rate [eGFR] <60 mL/min/1.73 m 2 or serum creatinin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
(18 reference statements)
2
11
0
Order By: Relevance
“…No conclusive evidence for an increase in lactic acidosis due to metformin was observed when analyzing the reported cases of lactic acidosis in the U.S. Food and Drug Administration´s Adverse Event reporting System, restricting the analysis to U.S. cases [ 150 ]. Support for this finding is provided by other studies [ 143 , 151 , 152 ]. Another research found; however that the use of metformin is associated with an increased risk of lactic acidosis in individuals with eGFR < 30 mL/min/1.73 m 2 [ 153 ].…”
Section: Metformin Monotherapy and Metformin-based Combination Thesupporting
confidence: 73%
“…No conclusive evidence for an increase in lactic acidosis due to metformin was observed when analyzing the reported cases of lactic acidosis in the U.S. Food and Drug Administration´s Adverse Event reporting System, restricting the analysis to U.S. cases [ 150 ]. Support for this finding is provided by other studies [ 143 , 151 , 152 ]. Another research found; however that the use of metformin is associated with an increased risk of lactic acidosis in individuals with eGFR < 30 mL/min/1.73 m 2 [ 153 ].…”
Section: Metformin Monotherapy and Metformin-based Combination Thesupporting
confidence: 73%
“…130,131 Additional more recent large studies showing a lack of risk for lactic acidosis above this eGFR cutoff now support this recommendation. 45,127,130 While the FDA does not explicitly state that dose adjustments are required above an eGFR of 30 mL/min/1.73 m 2 , we agree with the KDIGO guideline, which offers a practice point to halve the dose for an eGFR <45 mL/min/1.73 m 2 . Not mentioned by KDIGO is the FDA recommendation that metformin not be initiated in people with an eGFR <45 mL/min/1.73 m 2 , based upon the notion that these patients are likely to progress to an eGFR <30 mL/min/1.73 m 2 , wherein metformin would be contraindicated.…”
Section: Commentarysupporting
confidence: 61%
“…44 Another significant barrier is low patient awareness. 45 The net result of poor CKD awareness, limited education, as well as personal, financial, and institutional barriers, is the low understanding of the health risks associated with CKD, poor prioritization of CKD management, and reduced adherence to recommended care. 46,47 The use of "high points" and condensed versions of lengthy practice recommendations tailored for busy clinicians may improve their dissemination, acceptance, and implementation.…”
Section: Implementation and Challengesmentioning
confidence: 99%
“…29 An analogous study using data from the Veteran's Health Administration found no difference in lactic acidosis hospitalizations between metformin and sulfonylurea users who developed reduced kidney function. 30 In a cohort study using national-level data from Sweden, metformin demonstrated less risk of a composite endpoint of acidosis, serious infection, and all-cause mortality compared with insulin and other oral antihyperglycemic agents in the subgroup of patients with eGFR of 45-60 mL/min/1.73 m 2 . 31 It is recommended to continue metformin in those with eGFR of ≥45 mL/min/1.73 m 2 , titrate cautiously or halve the dose with eGFR of 30-44 mL/min/1.73 m 2 , and to discontinue with eGFR of <30 mL/min/1.73 m 2 and the dialysis population.…”
Section: Pharmacological Agents Metforminmentioning
confidence: 99%